A method for recovering black powder from waste lithium batteries
Through the pretreatment, heating and combustion, and pickling solid-liquid separation of waste lithium batteries, combined with the selective treatment of filter membrane, the problem of insufficient lithium purity in recycling of waste lithium iron phosphate batteries is solved, and efficient lithium ion recovery and purity improvement is achieved. .
Patent Information
- Application Number
- CN202410944915.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-15
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-07-15
AI Technical Summary
In the recycling and processing process of waste lithium iron phosphate batteries, the mechanical crushing process will destroy the physical and chemical properties of the positive electrode material, increase the difficulty of the lithium purification process, resulting in insufficient purity of recovered lithium, affecting the performance of the battery being prepared again.
A method of recycling black powder in waste lithium batteries is adopted, including pretreatment, heating and combustion, pickling and solid-liquid separation, and selective filter membranes are prepared by regulating the pore size of the filter membrane and quaternary amination modification to improve the purity of lithium ions.
This method significantly improves the purity of lithium ions, reaching 99.9941% or above, optimizes the recycling efficiency, and reduces environmental pollution and resource waste.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of recycling waste lithium batteries, and in particular relates to a method for recycling black powder in waste lithium batteries. Background Art
[0002] Although lithium iron phosphate batteries are slightly inferior to transition metal oxide batteries such as lithium nickel cobalt manganese oxide and lithium manganese oxide in terms of operating voltage platform and capacity density, their unique advantages lie in their excellent charge and discharge cycle life, unparalleled safety, excellent thermal stability and relatively low manufacturing cost. These characteristics make lithium iron phosphate batteries stand out in the power storage and power battery market that pursues long-lasting durability, economical affordability and ease of use, and become the preferred solution.
[0003] However, with the widespread application of lithium iron phosphate batteries and the rapid development of the industry, an issue that cannot be ignored has also emerged: the recycling and treatment of a large number of waste lithium iron phosphate batteries. The proper treatment of waste lithium iron phosphate batteries is not only an important part of resource recycling, but also the key to maintaining environmental sustainability.
[0004] At present, the recycling process of waste lithium iron phosphate batteries mainly includes the following steps: first, the battery is carefully classified according to its chemical composition; then, it is physically disassembled to separate the different components of the battery; then, it is calcined at high temperature and crushed and sorted to extract valuable materials; finally, the electrolyte is recovered and extracted. However, this process is not perfect and there are still certain challenges and problems.
[0005] For example, during the mechanical crushing process, the crushing of the shell, current collector and diaphragm of the waste polyanion battery will inevitably affect the physical and chemical properties of the positive electrode material to be recycled. On the one hand, the crushing process may destroy the neat arrangement of the positive electrode material crystals, resulting in a decrease in material performance; on the other hand, the mixing of copper, aluminum, phosphate, lithium ion electrolyte and binder increases the difficulty of the subsequent lithium purification process, which may result in insufficient purity of the recovered lithium, thereby affecting the performance of the battery prepared again. These problems have restricted the industrial application and market promotion of lithium iron phosphate batteries to a certain extent.
[0006] Therefore, how to optimize and improve the recycling process of waste lithium iron phosphate batteries, improve recycling efficiency and material purity, and reduce environmental pollution and resource waste is an important issue that needs to be solved urgently. Summary of the invention
[0007] The object of the present invention is to provide a method for recovering black powder in waste lithium batteries, so as to improve the purity of lithium obtained by recovering and separating the black powder.
[0008] The purpose of the present invention can be achieved through the following technical solutions:
[0009] A method for recovering black powder from waste lithium batteries comprises the following steps:
[0010] S1. Recycle waste lithium iron phosphate batteries, discharge, shear, crush, peel, grind, and demagnetize to obtain pre-treated black powder;
[0011] S2, adding sodium p-toluenesulfonate to the pretreated black powder and mixing; turning on the heater and pump of the fluidized bed to heat, pump air, and pump the pretreated black powder to the combustion chamber for combustion, cooling, and recovering the decarbonized and fluorinated black powder;
[0012] S3, pickling the decarbonized and fluorinated black powder, separating the solid and the liquid, and obtaining a solution A containing lithium ions, copper ions, and aluminum ions and a solid A containing iron phosphate; then filtering the solution A through a filter membrane, and taking the filtrate to obtain a pure lithium ion liquid.
[0013] As a preferred technical solution of the present invention, the preparation of the filter membrane comprises the following steps:
[0014] A1. Mix polyetheretherketone and concentrated sulfuric acid, stir at 45-55°C for 5-7h, transfer to an ice-water bath for precipitation, filter, wash and dry the solid phase to obtain material A;
[0015] A2, taking the material A, dimethyl sulfoxide, carbonyldiimidazole, and 1-(3-aminopropyl)imidazole, mixing them, stirring at 50-60° C. for 6-9 hours, transferring them to deionized water for precipitation, filtering, washing the solid phase, and drying to obtain material B;
[0016] A3, mix polyarylsulfone and anhydrous chloroform, add paraformaldehyde, trimethylsilyl chloride, and anhydrous tin tetrachloride, stir at 45-50°C for 5-6h, transfer to anhydrous ethanol for precipitation, filter, wash the solid phase, and dry to obtain material C;
[0017] A4, taking the material C and the trimethylamine aqueous solution, mixing, stirring at 40°C for 18-20h, dialyzing, and freeze-drying to obtain material D;
[0018] A5, take the material D, methanol, deionized water, ammonia water, zinc acetate, mix, ultrasonically disperse for 20-30 minutes, and obtain the first film-forming solution for standby use;
[0019] Take the material B and N-methylpyrrolidone, mix them, and stir for 2-3 hours to obtain the second film-forming solution for standby use;
[0020] A6. Mix the first membrane-forming liquid and the second membrane-forming liquid in a volume ratio of 1:1, stir at 45-55° C. for 2-3 hours, apply on a glass plate by a casting method, dry with hot air for 12-18 hours, cool in deionized water, wait for the film to fall off the glass plate, put the film into a sealed bag, soak in 0.25 mol / L sulfuric acid for 48 hours, soak in deionized water for half an hour, and repeat washing 3 times to obtain the filter membrane.
[0021] As a preferred technical solution of the present invention, in step A1, the dosage ratio of the polyetheretherketone and concentrated sulfuric acid is 30-40 g: 550-600 mL; the mass fraction of sulfuric acid in the concentrated sulfuric acid is 98%.
[0022] As a preferred technical solution of the present invention, in step A2, the mass ratio of the material A, dimethyl sulfoxide, carbonyldiimidazole and 1-(3-aminopropyl)imidazole is 6-8:100:1-1.2:0.6-0.7.
[0023] As a preferred technical solution of the present invention, in step A3, the dosage ratio of the polyarylsulfone, anhydrous chloroform, paraformaldehyde, trimethylchlorosilane and anhydrous tin tetrachloride is 7-8g:9-10g:50mL:0.8-1mL:0.12.
[0024] As a preferred technical solution of the present invention, in step A4, the dosage ratio of the material C and the trimethylamine aqueous solution is 8-10 g:50-70 mL; the mass fraction of trimethylamine in the trimethylamine aqueous solution is 15%.
[0025] As a preferred technical solution of the present invention, in step A5, the dosage ratio of material D, methanol, deionized water, ammonia water, and zinc acetate in the preparation of the first membrane-forming solution is 2-3g:10-12mL:10-12mL:1-2mL:1-2g; the concentration of the ammonia water is 4 mol / L.
[0026] As a preferred technical solution of the present invention, in step A5, the dosage ratio of the material B and N-methylpyrrolidone in the preparation of the second membrane-forming solution is 1-2g:5mL.
[0027] Beneficial effects of the present invention:
[0028] The invention discloses a method for recovering black powder in waste lithium batteries, which prepares a filter membrane with selective permeability to lithium ions by adjusting the pore size of the filter membrane and modifying it by quaternary ammonium, thereby improving the purity of lithium ions recovered and separated from the black powder. DETAILED DESCRIPTION
[0029] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0030] Example 1
[0031] A method for recovering black powder from waste lithium batteries comprises the following steps:
[0032] S1. Place 40kg of recycled waste lithium iron phosphate batteries in tap water containing 1.7% sodium chloride (mass concentration), discharge for 4 days, and then place them under solar radiation to dry the electrolyte inside the battery; then shear the battery 3 times to obtain broken blocks, so that the area ratio of the broken blocks (pole pieces) to the area of the battery is 30%; place the broken blocks in a stripping liquid (the volume ratio of glycerol to triethyl phosphate is 1:0.5), and be covered by the stripping liquid. The heating equipment is heated to 170°C, kept warm for 150 minutes, stirred, sieved, and separated to obtain solids and separation liquid. The solids are aluminum and copper foil, which are recovered; continue to heat the separation liquid containing flaky active substances, keep warm at 225°C for 200 minutes, and recover the stripping liquid to separate the flaky active substances. The flaky active substances are ground and demagnetized to obtain 10kg of pre-treated black powder;
[0033] S2, add 30g of sodium p-toluenesulfonate to the pretreated black powder and mix; turn on the heater and pump of the fluidized bed, heat, pump air, and pump the pretreated black powder to the combustion chamber to burn at 560°C, cool down, and recover 9.33kg of decarbonized and fluorinated black powder;
[0034] S3, the decarbonized and defluorinated black powder is pickled with 1 mol / L phosphoric acid, and the solid-liquid separation is performed to obtain a solution A containing lithium ions, copper ions, and aluminum ions and a solid A containing iron phosphate; then the solution A is filtered through a filter membrane, and the filtrate is taken to obtain a pure lithium ion liquid with a lithium ion purity of 99.9941%.
[0035] The preparation of the filter membrane comprises the following steps:
[0036] A1. Mix polyetheretherketone and concentrated sulfuric acid, stir at 45°C for 5h, transfer to an ice-water bath for precipitation, filter, wash the solid phase, and dry to obtain material A; the dosage ratio of polyetheretherketone and concentrated sulfuric acid is 30g:5500mL; the mass fraction of sulfuric acid in the concentrated sulfuric acid is 98%;
[0037] A2. Mix the material A, dimethyl sulfoxide, carbonyldiimidazole and 1-(3-aminopropyl)imidazole, stir at 50°C for 6h, transfer to deionized water for precipitation, filter, wash the solid phase, and dry to obtain material B; the mass ratio of the material A, dimethyl sulfoxide, carbonyldiimidazole and 1-(3-aminopropyl)imidazole is 6:100:1:0.6;
[0038] A3, take polyarylsulfone and anhydrous chloroform, mix, add paraformaldehyde, trimethylchlorosilane, anhydrous tin tetrachloride, stir at 45 ° C for 5 hours, transfer to anhydrous ethanol for precipitation, filter, wash the solid phase, dry, and obtain material C; the amount ratio of polyarylsulfone, anhydrous chloroform, paraformaldehyde, trimethylchlorosilane, anhydrous tin tetrachloride is 7g:9g:50mL:0.8mL:0.12;
[0039] A4, taking the material C and the trimethylamine aqueous solution, mixing, stirring at 40 ° C for 18 hours, dialyzing, freeze-drying, and obtaining material D; the dosage ratio of the material C and the trimethylamine aqueous solution is 8g:50mL; the mass fraction of trimethylamine in the trimethylamine aqueous solution is 15%;
[0040] A5. Mix the material D, methanol, deionized water, ammonia water and zinc acetate, and perform ultrasonic dispersion for 20 minutes to obtain the first membrane-forming solution for standby use; the dosage ratio of the material D, methanol, deionized water, ammonia water and zinc acetate is 2g:10mL:10mL:1mL:1g; the concentration of the ammonia water is 4mol / L;
[0041] The material B and N-methylpyrrolidone are mixed and stirred for 2 hours to obtain a second membrane-forming solution for standby use; the dosage ratio of the material B and N-methylpyrrolidone is 1g:5mL;
[0042] A6. Mix the first film-forming liquid and the second film-forming liquid in a volume ratio of 1:1, stir at 45°C for 2 hours, apply on a glass plate by a casting method, dry with hot air for 12 hours, cool in deionized water, wait for the film to fall off the glass plate, put the film into a sealed bag, soak in 0.25 mol / L sulfuric acid for 48 hours, soak in deionized water for half an hour, and repeat washing 3 times to obtain the filter membrane.
[0043] Example 2
[0044] A method for recovering black powder from waste lithium batteries comprises the following steps:
[0045] S1. Place 40kg of recycled waste lithium iron phosphate batteries in tap water containing 1.7% sodium chloride (mass concentration), discharge for 4 days, and then place them under solar radiation to dry the electrolyte inside the battery; then shear the battery 3 times to obtain broken blocks, so that the area ratio of the broken blocks (pole pieces) to the area of the battery is 30%; place the broken blocks in a stripping liquid (the volume ratio of glycerol to triethyl phosphate is 1:0.5), and be covered by the stripping liquid. The heating equipment is heated to 170°C, kept warm for 150 minutes, stirred, sieved, and separated to obtain solids and separation liquid. The solids are aluminum and copper foil, which are recovered; continue to heat the separation liquid containing flaky active substances, keep warm at 225°C for 200 minutes, and recover the stripping liquid to separate the flaky active substances. The flaky active substances are ground and demagnetized to obtain 10kg of pre-treated black powder;
[0046] S2, add 30g of sodium p-toluenesulfonate to the pretreated black powder and mix; turn on the heater and pump of the fluidized bed, heat, pump air, and pump the pretreated black powder to the combustion chamber to burn at 560°C, cool down, and recover 9.30kg of decarbonized and fluorinated black powder;
[0047] S3, the decarbonized and defluorinated black powder is pickled with 1 mol / L phosphoric acid, and the solid-liquid separation is performed to obtain a solution A containing lithium ions, copper ions, and aluminum ions and a solid A containing iron phosphate; then the solution A is filtered through a filter membrane, and the filtrate is taken to obtain a pure lithium ion liquid with a lithium ion purity of 99.9944%.
[0048] The preparation of the filter membrane comprises the following steps:
[0049] A1. Mix polyetheretherketone and concentrated sulfuric acid, stir at 50°C for 6h, transfer to an ice-water bath for precipitation, filter, wash the solid phase, and dry to obtain material A; the dosage ratio of polyetheretherketone and concentrated sulfuric acid is 35g:580mL; the mass fraction of sulfuric acid in the concentrated sulfuric acid is 98%;
[0050] A2. Mix the material A, dimethyl sulfoxide, carbonyldiimidazole and 1-(3-aminopropyl)imidazole, stir at 55° C. for 7.5 h, transfer to deionized water for precipitation, filter, wash the solid phase, and dry to obtain material B; the mass ratio of the material A, dimethyl sulfoxide, carbonyldiimidazole and 1-(3-aminopropyl)imidazole is 7:100:1.1:0.65;
[0051] A3, take polyarylsulfone and anhydrous chloroform, mix, add paraformaldehyde, trimethylchlorosilane, anhydrous tin tetrachloride, stir at 48 ° C for 5.5 hours, transfer to anhydrous ethanol for precipitation, filter, wash the solid phase, dry, and obtain material C; the dosage ratio of polyarylsulfone, anhydrous chloroform, paraformaldehyde, trimethylchlorosilane, anhydrous tin tetrachloride is 7.5g:9.5g:50mL:0.9mL:0.12;
[0052] A4, taking the material C and the trimethylamine aqueous solution, mixing, stirring at 40 ° C for 19 hours, dialyzing, and freeze-drying to obtain material D; the dosage ratio of the material C and the trimethylamine aqueous solution is 9g:60mL; the mass fraction of trimethylamine in the trimethylamine aqueous solution is 15%;
[0053] A5, take the material D, methanol, deionized water, ammonia water, zinc acetate, mix, ultrasonically disperse for 25 minutes, and obtain the first membrane-forming solution for standby use; the dosage ratio of the material D, methanol, deionized water, ammonia water, and zinc acetate is 2.5g:11mL:11mL:1.5mL:1.5g; the concentration of the ammonia water is 4mol / L;
[0054] The material B and N-methylpyrrolidone were mixed and stirred for 2.5 hours to obtain a second membrane-forming solution for standby use; the dosage ratio of the material B to N-methylpyrrolidone was 1.5 g: 5 mL;
[0055] A6. Mix the first film-forming liquid and the second film-forming liquid in a volume ratio of 1:1, stir at 50°C for 2.5 hours, apply on a glass plate by a casting method, dry with hot air for 15 hours, cool in deionized water, wait for the film to fall off the glass plate, put the film into a sealed bag, soak in 0.25 mol / L sulfuric acid for 48 hours, soak in deionized water for half an hour, and repeat washing 3 times to obtain the filter membrane.
[0056] Example 3
[0057] A method for recovering black powder from waste lithium batteries comprises the following steps:
[0058] S1. Place 40kg of recycled waste lithium iron phosphate batteries in tap water containing 1.7% sodium chloride (mass concentration), discharge for 4 days, and then place them under solar radiation to dry the electrolyte inside the battery; then shear the battery 3 times to obtain broken blocks, so that the area ratio of the broken blocks (pole pieces) to the area of the battery is 30%; place the broken blocks in a stripping liquid (the volume ratio of glycerol to triethyl phosphate is 1:0.5), and be covered by the stripping liquid. The heating equipment is heated to 170°C, kept warm for 150 minutes, stirred, sieved, and separated to obtain solids and separation liquid. The solids are aluminum and copper foil, which are recovered; continue to heat the separation liquid containing flaky active substances, keep warm at 225°C for 200 minutes, and recover the stripping liquid to separate the flaky active substances. The flaky active substances are ground and demagnetized to obtain 10kg of pre-treated black powder;
[0059] S2, add 30g of sodium p-toluenesulfonate to the pretreated black powder and mix; turn on the heater and pump of the fluidized bed, heat, pump air, and pump the pretreated black powder to the combustion chamber to burn at 560°C, cool down, and recover 9.31kg of decarbonized and fluorinated black powder;
[0060] S3, the decarbonized and defluorinated black powder is pickled with 1 mol / L phosphoric acid, and the solid-liquid separation is performed to obtain a solution A containing lithium ions, copper ions, and aluminum ions and a solid A containing iron phosphate; then the solution A is filtered through a filter membrane, and the filtrate is taken to obtain a pure lithium ion liquid with a lithium ion purity of 99.9942%.
[0061] The preparation of the filter membrane comprises the following steps:
[0062] A1. Mix polyetheretherketone and concentrated sulfuric acid, stir at 55°C for 7h, transfer to an ice-water bath for precipitation, filter, wash the solid phase, and dry to obtain material A; the polyetheretherketone and concentrated sulfuric acid have a ratio of 40g:600mL; the mass fraction of sulfuric acid in the concentrated sulfuric acid is 98%;
[0063] A2. Mix the material A, dimethyl sulfoxide, carbonyldiimidazole and 1-(3-aminopropyl)imidazole, stir at 60° C. for 9 h, transfer to deionized water for precipitation, filter, wash the solid phase, and dry to obtain material B; the mass ratio of the material A, dimethyl sulfoxide, carbonyldiimidazole and 1-(3-aminopropyl)imidazole is 8:100:1.2:0.7;
[0064] A3, take polyarylsulfone and anhydrous chloroform, add paraformaldehyde, trimethylchlorosilane and anhydrous tin tetrachloride, stir at 50°C for 6h, transfer to anhydrous ethanol for precipitation, filter, wash and dry the solid phase to obtain material C; the dosage ratio of polyarylsulfone, anhydrous chloroform, paraformaldehyde, trimethylchlorosilane and anhydrous tin tetrachloride is 8g:10g:50mL:1mL:0.12;
[0065] A4, taking the material C and the trimethylamine aqueous solution, mixing, stirring at 40 ° C for 20 hours, dialyzing, and freeze-drying to obtain material D; the dosage ratio of the material C and the trimethylamine aqueous solution is 10g:70mL; the mass fraction of trimethylamine in the trimethylamine aqueous solution is 15%;
[0066] A5, take the material D, methanol, deionized water, ammonia water, zinc acetate, mix, ultrasonically disperse for 30 minutes, and obtain the first membrane-forming solution for standby use; the dosage ratio of the material D, methanol, deionized water, ammonia water, and zinc acetate is 3g:12mL:12mL:2mL:2g; the concentration of the ammonia water is 4mol / L;
[0067] The material B and N-methylpyrrolidone are mixed and stirred for 3 hours to obtain a second membrane-forming solution for standby use; the dosage ratio of the material B and N-methylpyrrolidone is 2g:5mL;
[0068] A6. Mix the first film-forming liquid and the second film-forming liquid in a volume ratio of 1:1, stir at 55°C for 3 hours, apply on a glass plate by a casting method, dry with hot air for 18 hours, cool in deionized water, wait for the film to fall off the glass plate, put the film into a sealed bag, soak in 0.25 mol / L sulfuric acid for 48 hours, soak in deionized water for half an hour, and repeat washing 3 times to obtain the filter membrane.
[0069] Comparative Example 1
[0070] The difference from Example 1 is that the preparation of the filter membrane only includes the filter membrane prepared from the first membrane-forming solution, thereby obtaining a pure lithium ion solution with a lithium ion purity of 81.3452%.
[0071] Comparative Example 2
[0072] The difference from Example 1 is that the preparation of the filter membrane only includes the filter membrane prepared from the second membrane-forming solution, thereby obtaining a pure lithium ion solution with a lithium ion purity of 79.2214%.
[0073] Comparative Example 3
[0074] The difference from Example 1 is that in the preparation process of the filter membrane, the mass ratio of material A, dimethyl sulfoxide, carbonyldiimidazole, and 1-(3-aminopropyl)imidazole in step A2 is 6:100:1.6:0; thereby obtaining a pure lithium ion liquid with a lithium ion purity of 91.2471%.
[0075] Comparative Example 4
[0076] The difference from Example 1 is that in the preparation process of the filter membrane, the mass ratio of material A, dimethyl sulfoxide, carbonyldiimidazole, and 1-(3-aminopropyl)imidazole in step A2 is 6:100:0:1.6; thereby obtaining a pure lithium ion liquid with a lithium ion purity of 91.2891%.
[0077] Comparative Example 5
[0078] The difference from Example 1 is that the preparation of the filter membrane includes the following steps:
[0079] A1. Mix polyetheretherketone and concentrated sulfuric acid, stir at 45°C for 5h, transfer to an ice-water bath for precipitation, filter, wash the solid phase, and dry to obtain material A; the dosage ratio of polyetheretherketone and concentrated sulfuric acid is 30g:5500mL; the mass fraction of sulfuric acid in the concentrated sulfuric acid is 98%;
[0080] A2. Mix the material A, dimethyl sulfoxide, carbonyldiimidazole and 1-(3-aminopropyl)imidazole, stir at 50°C for 6h, transfer to deionized water for precipitation, filter, wash the solid phase, and dry to obtain material B; the mass ratio of the material A, dimethyl sulfoxide, carbonyldiimidazole and 1-(3-aminopropyl)imidazole is 6:100:1:0.6;
[0081] A3, take polyarylsulfone and anhydrous chloroform, mix, add paraformaldehyde, trimethylchlorosilane, anhydrous tin tetrachloride, stir at 45 ° C for 5 hours, transfer to anhydrous ethanol for precipitation, filter, wash the solid phase, dry, and obtain material C; the amount ratio of polyarylsulfone, anhydrous chloroform, paraformaldehyde, trimethylchlorosilane, anhydrous tin tetrachloride is 7g:9g:50mL:0.8mL:0.12;
[0082] A4, take the material C, methanol, deionized water, ammonia water, zinc acetate, mix, ultrasonically disperse for 20 minutes, and obtain the first membrane-forming solution for standby use; the dosage ratio of the material C, methanol, deionized water, ammonia water, and zinc acetate is 2g:10mL:10mL:1mL:1g; the concentration of the ammonia water is 4mol / L;
[0083] The material B and N-methylpyrrolidone are mixed and stirred for 2 hours to obtain a second membrane-forming solution for standby use; the dosage ratio of the material B and N-methylpyrrolidone is 1g:5mL;
[0084] A5. Mix the first film-forming liquid and the second film-forming liquid in a volume ratio of 1:1, stir at 45°C for 2 hours, apply on a glass plate by a casting method, dry with hot air for 12 hours, cool in deionized water, wait for the film to fall off the glass plate, put the film into a sealed bag, soak in 0.25 mol / L sulfuric acid for 48 hours, soak in deionized water for half an hour, and repeat washing 3 times to obtain the filter membrane.
[0085] Thus, a pure lithium ion liquid with a lithium ion purity of 88.7145% is obtained.
[0086] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for recovering black powder from waste lithium batteries, characterized in that: The following steps are involved: S1. Recycle waste lithium iron phosphate batteries, discharge, shear, crush, peel, grind, and demagnetize to obtain pre-treated black powder; S2, adding sodium p-toluenesulfonate to the pretreated black powder and mixing; turning on the heater and pump of the fluidized bed to heat, pump air, and pump the pretreated black powder to the combustion chamber for combustion, cooling, and recovering the decarbonized and fluorinated black powder; S3, pickling the decarbonized and fluorinated black powder, separating the solid and the liquid, and obtaining a solution A containing lithium ions, copper ions, and aluminum ions and a solid A containing iron phosphate; then filtering the solution A through a filter membrane, and taking the filtrate to obtain a pure lithium ion liquid; The preparation of the filter membrane comprises the following steps: A1. Mix polyetheretherketone and concentrated sulfuric acid, stir at 45-55°C for 5-7h, transfer to an ice-water bath for precipitation, filter, wash and dry the solid phase to obtain material A; A2, taking the material A, dimethyl sulfoxide, carbonyldiimidazole, and 1-(3-aminopropyl)imidazole, mixing them, stirring at 50-60°C for 6-9h, transferring them to deionized water for precipitation, filtering, washing the solid phase, and drying to obtain material B; A3, mix polyarylsulfone and anhydrous chloroform, add paraformaldehyde, trimethylsilyl chloride, and anhydrous tin tetrachloride, stir at 45-50°C for 5-6h, transfer to anhydrous ethanol for precipitation, filter, wash the solid phase, and dry to obtain material C; A4, taking the material C and the trimethylamine aqueous solution, mixing, stirring at 40°C for 18-20h, dialyzing, and freeze-drying to obtain material D; A5, take the material D, methanol, deionized water, ammonia water, zinc acetate, mix, ultrasonically disperse for 20-30 minutes, and obtain the first film-forming solution for standby use; Take the material B and N-methylpyrrolidone, mix them, and stir for 2-3 hours to obtain the second film-forming solution for standby use; A6. Mix the first film-forming liquid and the second film-forming liquid in a volume ratio of 1:1, stir at 45-55°C for 2-3h, apply on a glass plate by a casting method, dry with hot air for 12-18h, cool in deionized water, wait for the film to fall off the glass plate, put the film into a sealed bag, soak in 0.25mol / L sulfuric acid for 48h, soak in deionized water for half an hour, and repeat washing 3 times to obtain the filter membrane.
2. The method for recovering black powder from waste lithium batteries according to claim 1, characterized in that: In step A1, the dosage ratio of the polyetheretherketone and concentrated sulfuric acid is 30-40 g: 550-600 mL; the mass fraction of sulfuric acid in the concentrated sulfuric acid is 98%.
3. The method for recovering black powder from waste lithium batteries according to claim 1, characterized in that: In step A2, the mass ratio of material A, dimethyl sulfoxide, carbonyldiimidazole and 1-(3-aminopropyl)imidazole is 6-8:100:1-1.2:0.6-0.
7.
4. The method for recovering black powder from waste lithium batteries according to claim 1, characterized in that: In step A3, the dosage ratio of the polyarylsulfone, anhydrous chloroform, paraformaldehyde, trimethylchlorosilane, and anhydrous tin tetrachloride is 7-8 g: 9-10 g: 50 mL: 0.8-1 mL: 0.12 g.
5. The method for recovering black powder from waste lithium batteries according to claim 1, characterized in that: In step A4, the dosage ratio of the material C and the trimethylamine aqueous solution is 8-10 g: 50-70 mL; the mass fraction of trimethylamine in the trimethylamine aqueous solution is 15%.
6. The method for recovering black powder from waste lithium batteries according to claim 1, characterized in that: In step A5, the dosage ratio of the material D, methanol, deionized water, ammonia water and zinc acetate in the preparation of the first membrane-forming solution is 2-3g:10-12mL:10-12mL:1-2mL:1-2g; the concentration of the ammonia water is 4mol / L.
7. The method for recovering black powder from waste lithium batteries according to claim 1, characterized in that: In step A5, the dosage ratio of the material B and N-methylpyrrolidone in the preparation of the second membrane-forming solution is 1-2g:5mL.
